Development of a Prototype for the Quality Control of Bovine Meat Determined by its Organoleptic Characteristics, based on an Automatic Inspection System for Artificial Vision (Latin-American Journal of Computing, 2017)
The world beef market is in full growth and with unsatisfied demands and prices up and these depend very much on their quality when arriving at the final consumer, while the national market, our country also has a future potential in the meat industry. In the present investigation is to evaluate the sensory characteristics of color and texture by means of the presence of a bovine meat sample in the system whose final result will be the acceptance or negation of its organoleptic quality. The system is constituted by a transport band in charge of taking the sample to a capsule where both the Lighting System (LS) and the Computer Vision System (CVS) are located, and when leaving there it will be automatically classified by an actuator, guaranteeing less manipulation and estimation of time by human intervention throughout the process while providing greater security to the final consumer about the meat that is entering their home.